2017
DOI: 10.5799/jcei.328751
|View full text |Cite
|
Sign up to set email alerts
|

CD3 Positive Gastric Plasmablastic Lymphoma in A HIV Negative Patient: A Case Report

Abstract: Plasmablastic lymphoma is a rare and aggressive lymphoma characterized by the diffuse proliferation of large neoplastic cells resembling immunoblasts with an immunophenotype of plasma cells. A 47-year-old male was referred to our hospital with gastrointestinal bleeding, and a mass, 10 cm in diameter, was detected. An endoscopic biopsy was performed subsequently. A histopathological examination of the biopsy material revealed ulcer, alterations associated with ulcer, and further presented a diffuse infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The majority of the gastrointestinal tract PBLs have been described in the stomach, small intestine, and colon as case reports and small case series. 18 -26 Herein, we report on 17 patients with gastrointestinal tract PBLs focusing on the morphological and immunohistochemical features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the gastrointestinal tract PBLs have been described in the stomach, small intestine, and colon as case reports and small case series. 18 -26 Herein, we report on 17 patients with gastrointestinal tract PBLs focusing on the morphological and immunohistochemical features.…”
Section: Discussionmentioning
confidence: 99%
“…8 The findings of the present study show comparable features to those reported in the case studies and series on gastrointestinal tract PBLs. 18 -26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations